Cover Image. (16th April 2018) - Hoffmann, P.; Flege, S.; Ensinger, W.; Wolf, F.; Weber, C.; Seeberg, S.; Sander, J.; Schultz, J.; Krekel, C.; Tagle, R.; Wittkopp, A.
Abstract : The cover image, by Peter Hoffmann et al., is based on the Research Article MA‐XRF investigation of the Altenberg Retable from 1330, DOI:10.1002/xrs.2829 . Photo credit: Städel Museum, Frankfurt am Main / 3D‐reconstruction: Yannic Jäckel